Model Pengasuhan Orangtua dengan Anak Disabilitas Netra - Fadhilah Putri Gemala; Ati Kusmawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research aims to find out what parenting models for parents with children with visual disabilities can be applied. This research uses a qualitative approach with a literature study approach through journals, books, and previous research. The result of the research is that children with visual disabilities have different parenting patterns from parents with other disabilities or non-disabilities. Children with visual disabilities must be given the best during their golden age and after that period give confidence and independence to children, after adolescence children have friends and parents must recognize and control children's friendships so as not to fall into something wrong, when children with visual disabilities grow up parents help children to be able to make the best decisions for themselves until children can make rational decisions and with mature thinking.